Proselytizing, Building, and Serving: Latter-day Saint Missionaries in Manitoba and Eastern Canada, 1897-1942. (September 2021) - Brassard, Brooke Kathleen
This article will consider missionary work performed in Manitoba and Eastern Canada, and how The Church of Jesus Christ of Latter-day Saints progressed toward integration into Canadian society as another established minority religion searching for potential new members. By navigating through their Canadian settings, Latter-day Saint missionaries adjusted themselves and their Church to local expectations and environments, and constructed a new home for Mormonism in Canada. Three ways that Latter-day Saint missionaries negotiated their place in Canada include evolving relationships with the Canadian public through missionary encounters, renting meeting spaces from fraternal organizations and then constructing their own meetinghouses, and organizing local, auxiliary organizations that aided non-members. The Canadian context, the Latter-day Saint missionary experience, and the growth of The Church of Jesus Christ of Latter-day Saints in Canada, reveals a process of negotiation. There exists a tension between integration and otherness. Latter-day Saints balanced this tension by on some levels maintaining their distinctiveness, while at the same time blending into Canadian expectations. How the Latter-day Saint missionaries responded to these barriers, the challenges related to communicating with the Canadian public, finding spaces to congregate, local leadership roles, and participating in different aspects of Canadian society, tells a story of a new religion integrating into a new environment.